Correlation of left atrial strain with left ventricular end-diastolic pressure in patients with coronary artery disease and preserved left ventricular ejection faction. (8th February 2021) - Ohara, Y; Yoshimura, Y; Fukuoka, Y; Tanioka, K; Yamamoto, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Elevated left ventricular (LV) filling pressures are the main physiologic consequence of LV diastolic dysfunction. Left atrial (LA) strain was recently found useful to predict elevated LV filling pressures noninvasively. However, there are few reports on the role of LA strain when predicting LV filling pressure in patients with coronary artery disease (CAD). The aim of this study was to explore the correlation between LA strain and LV end-diastolic pressure (LVEDP) in patients with CAD and preserved LV ejection fraction. Methods: Fifty-four patients with stable CAD were enrolled. Global atrial longitudinal strain was measured by averaging all atrial segments. Resorvoir (S-LAs), conduit (S-LAe), and contractile (S-LAa) phase strain were obtained. LVEDP was invasively obtained by left heart catheterization. Results: Patients were divided into two groups: elevated LVEDP group (LVEDP > 15mmHg group: n = 23) and normal LVEDP group (LVEDP ≤ 15mmHg group: n = 31). Elevated LVEDP group showed significantly decreased S-LAs and S-LAa (S-LAs: 21.3 ± 7.2% vs. 27.5 ± 7.8%, p < 0.005; S-LAa: 9.7 ± 3.3% vs. 14.6 ± 3.4%, p < 0.0001). However, E/Ea and S-LAe were not significantly different between the two groups. LVEDP significantly correlated with S-LAa (r=-0.596, p < 0.0001) and S-LAs (r=-0.431, p < 0.001). Receiver operating characteristics curve analysis showed that S-LAa could predict elevated LVEDP (AUC = 0.84) and a cut-off value of S-LAa < 11.6% was able to most accurately identify patients with elevated LVEDP. Conclusions: LA strain, especially S-LAa, provided additional diagnostic value for the noninvasive assessment of LV filling pressure in CAD patients with preserved LV ejection fraction.